Quality assessment of the outsourcing services of the furniture and layout intervention in a public organization - Gouvêa, Maria Aparecida; Pinto, Ricardo Lopes; Oliveira, Braulio (Revista de Administração da UFSM, 2015)
This study aimed to identify, within the framework of a public organization, indicators allowing an assessment of the quality of outsourced service maintenance of layout according to the perspectives of users, of contract fiscals and of the responsible for service providers. Through the statistical technique of structural equations modeling, the definition of constructs directly relevant to the measurement of quality of service of maintenance of layout has been obtained. On the basis of the results of four surveys (a quantitative one with service users and three qualitative, each of them with each segment: users, fiscals and service providers) it was possible to compare the rankings of the aspects that lead to perceived quality of the services in accordance with the three segments of interest in this work. The main indicators and their assessments may be considered by the company focused in this study as items in the drawing up of contracts between suppliers and contracting part and as references in monitoring the provision of maintenance of layout.